2005
DOI: 10.1111/j.1440-1797.2005.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Wasp envenomation‐induced acute renal failure: A report of three cases (Case Report)

Abstract: Acute renal failure is an unusual complication of wasp stings. We report three cases who developed acute renal failure after multiple wasp stings (Vespa magnifica). Two patients had evidence of intravascular haemolysis and rhabdomyolysis whereas one patient investigation showed no evidence of intravascular haemolysis or rhabdomyolysis. All three cases had impaired liver functions. Oligo-anuria was seen in all three of the patients and all of them required dialytic support. One patient died of massive gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 20 publications
2
26
0
3
Order By: Relevance
“…Intravascular hemolysis has been reported in most reports discussing wasp sting complications in the literature [4,8,9,11,13,14,22] as in our reviewed patients, in which six had anemia, three of which in turn had a hematocrit of less than 25 which could not be explained only from a dilutional effect due to volume overload; hemolysis has previously been noted as a major reaction in ARF [3,11]. Thrombocytopenia has also been found in one patient reported from India, and the authors believed that the thrombocytopenia was a direct result of the effect of the venom on the platelets [21].…”
Section: Discussionmentioning
confidence: 60%
“…Intravascular hemolysis has been reported in most reports discussing wasp sting complications in the literature [4,8,9,11,13,14,22] as in our reviewed patients, in which six had anemia, three of which in turn had a hematocrit of less than 25 which could not be explained only from a dilutional effect due to volume overload; hemolysis has previously been noted as a major reaction in ARF [3,11]. Thrombocytopenia has also been found in one patient reported from India, and the authors believed that the thrombocytopenia was a direct result of the effect of the venom on the platelets [21].…”
Section: Discussionmentioning
confidence: 60%
“…Herein, we demonstrated that PPV induced mild focal acute tubular necrosis. In fact, tubulointerstitial nephritis and acute tubular necrosis are often observed in patients envenomed by wasps (8,(11)(12)(13). Moreover, cell viability and membrane integrity decreased when the survival of untreated cells was compared with the mean percentage of surviving MDCK cells under a given PPV concentration using the LDH assay.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that the underlying mechanism of ARF involves a direct nephrotoxic effect following wasp poisoning, which may then result in tubulointerstitial nephritis and acute tubular necrosis, possibly in association with hemolysis or rhabdomyolysis (9)(10)(11)(12)(13)(14). In fact, mastoparans, polycationic peptides isolated from PPV, cause apoptosis involving caspase-signaling pathways with mitochondrial damage, and cytokine activation (15).…”
Section: Introductionmentioning
confidence: 99%
“…Melittin is the main pathogenic factor, containing a neurotoxin, hemolytic toxin and mast cell degranulation compounds. Following a sting, wasp venom can induce multi-organ injury, including renal [8,9], nervous system [10][11][12], cardiac [13], liver [14,15], and respiratory system [16][17][18] injury, due to its complexity. Wasp venom not only causes direct damage to human organs and tissues, but also aggravates the condition via the allergic reaction and inflammatory reaction [19].…”
Section: Discussionmentioning
confidence: 99%